(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Nanoparticles (NPs) have attracted considerable attention in contemporary biomedical research, especially for use in wound care. Among others, zinc oxide (ZnO) nanoparticles have shown promising antioxidant and antibacterial activities, making them ideal for wound healing and infection management. Because of their capacity to alleviate oxidative stress, defend against microbial infections, and stimulate cell regeneration, they have emerged as a novel therapeutic strategy in addressing wound healing concerns. Although they have potential, issues with toxicity, biocompatibility, and long-term stability remain to be addressed for medical applications of safe and effective nanocolloids. Objective: Here, we explore the antioxidant and antibacterial efficacy of ZnO nanoparticles to determine their potential as a therapeutic agent for wound healing. This review explores the ways ZnO nanoparticles promote tissue healing, their effect on microbial inhibition, and the barriers preventing clinical translation. This study also sheds light on possible approaches to enhance ZnO-based formulations for future biomedical applications. Methodology: We developed a structured questionnaire that was disseminated to healthcare professionals, biomedical researchers and nanotech experts to collect both quantitative and qualitative data. Data on awareness levels and perceptions regarding ZnO-based wound healing therapies and their safety and effectiveness were assessed. An extensive literature review was performed on peer-reviewed sources from PubMed, Scopus, Web of Science and Google Scholar to build a theoretical foundation for the biomedical application of ZnO nanoparticles. Key Findings: The results of the study showed that ZnO nanoparticles demonstrated an effective antibacterial activity against wound associated microorganisms, thus minimizing the chances of secondary infection. They also have anticancer and wound healing properties due to their antioxidant potential, which reduce oxidative stress, a critical contributor to delayed wound healing. The respondents endorsed the advantages offered by ZnO nanoparticles, as upregulation of fibroblast proliferation, matrix deposition, and overall enhancement of tissue regeneration. Nevertheless, issues surrounding cytotoxicity at elevated concentrations, stability in biological microenvironments, and aggregated body response (e.g., inflammation) still pose critical challenges. In addition, this investigation also added to the growing interest towards the development of biodegradable ZnO nanocomposites in order to investigate safety issues and increase their clinical relevance. Future Directions: Moreover, with potential and existing limitations need biocompatible ZnO with controlled release mechanisms to minimize toxicity and maximize therapeutic benefits. But it is possible that new improved advanced coating techniques, innovative hybrid nanomaterials, and tailored nanoparticle therapies can provide some answers to enhance specificity of drug delivery and wounds for instance. Rules and regulations should be established to guide the safe and ethical use of ZnO-based nanomedicine by regulatory agencies. Moreover, academic and industrial interdisciplinary collaboration between material scientists, medical experts, and pharmaceutical industries is also vital to transition ZnO nanoparticle studies to adoptable, scalable clinical wound healing therapies. Conclusion: ZnO nanoparticles are promising nanomedicine-driven wound healing agents with strong antioxidant and antibacterial properties leading to fast recovery and low chances of infection. They possess numerous advantages; however, further studies, optimization, and regulatory approvals of formulations are needed for their clinical translation. Combating with underlying difficulties and incorporating biocompatible nanotechnology, ZnO-directed therapeutics can systematically improve the key role of wound care and regenerative medicine in modern health care.